PEMBERIAN MINUMAN KUNYIT ASAM TERHADAP PENURUNAN SKALA NYERI HAID (DISMENOREA) - Novy Ramini harahap; Nurrahmaton -; Sri Juliani; Mira Sasmita (Jurnal Maternitas Kebidanan, 2023)
Introduction: Physical weakness, lack of mobility, and stress are among issues that women face with dysmenorrhea. Menstrual pain is frequently accompanied by nausea, dizziness, and weakness. According to WHO data from 2017, it was discovered that the global incidence of dysmenorrhea was more than 50% of women worldwide. Objective:The study aimed to see if administering tamarind turmeric drinkinging reduced dysmenorrhea in Lingkungan V, Sumber Karya Binjai Village in 2021. Method: This was a Pre-Experimental study using the One Group Pretest-Posttest Design method. Purposive sampling was used to gather a sample of 10 participants from a population of 25 teenagers who suffer menstrual discomfort during menstruation. The data was analyzed using univariate and bivariate analyses, as well as the paired t-test The Result: The results showed that from 10 respondents, a decrease in menstrual pain level before giving turmeric drinkinging was obtained, namely severe pain by 5 respondents (50.0%), a mean of 3.80 with a standard deviation of 0.919. Reduction in Menstrual Pain Scale After Administering Turmeric Tamarind, namely No Pain by 7 respondents (70.0%), the mean was 2.10 with a standard deviation of 0.568. The average score for relieving menstruation pain after consuming tamarind turmeric drinking was 5.50. This demonstrated after receiving the turmeric tamarind drinking, the respondents' Menstrual Pain level decreased. The Wilcoxon test yielded a p-value of 0.004<0.05.Conclusion: The results revealed that administering tamarind turmeric drinkings has an effect on lowering the menstrual pain scale (dysmenorrhea) in Ward V, Sumber Karya Binjai Village 2021. It is believed that young ladies would be able to use tamarind turmeric treatment to reduce the severity of period discomfort.